(untitled) (Medicine Today, 2020)
Introduction: Hypertensive disorders are the commonest complications during pregnancy responsible for maternal and foetal mortality and morbidity. The aim of the study was to determine the magnitude of percentage of disorders in admitted pregnant women. A retrospective study was done to determine the pattern of disorders during pregnancy among the admitted pregnant women National Medical Institute Hospital. This study was done during January 2017 to December 2017 at Dhaka National Medical Institute Hospital. Materials and Methods: 3276 pregnant women admitted had medical disorders (406) with 12.39% at the age of reproduction (20-35 years). Results: The commonest disorders were hypertensive disease of pregnancy (45.32%), urinary tract infection (14.78%), gestational diabetic mellitus (10.84%), anaemia (7.39%), bronchial asthma (6.40%) respiratory infectious conditions (5.42%), viral infections (3.94%), thyroid disorder (3.45%), and cardiac disease (2.45%). Conclusion: Hypertensive disorder is the most common medical disorder of pregnancy followed by urinary tract infection, gestational diabetic mellitus, anaemia, bronchial asthma respiratory infectious conditions, viral infections, thyroid disorder and cardiac disease in order. Medicine Today 2020 Vol.32(2): 122-125